Leadership Style in Vocational High Schools (SMK) - Risha Febriyanti; Hasan Maksum; M. Giatman; Wawan Purwanto; Ridwan (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This study explores the influence of the principal's leadership style on teacher performance and student learning outcomes in Vocational High Schools (SMK). Research findings show that democratic and transformational leadership styles are most effective in creating a positive and productive school environment. The findings show that democratic and transformational leadership styles are the most effective in creating a positive and productive school environment. Leadership, with transformational, its focus on values such as empowerment and long-term, can inspire and motivate teachers and values while encouraging innovation and high-level commitment. such as empowerment and long-term, can inspire and motivate teachers and students while encouraging high-level innovation and commitment. Democratic leadership leadership, which encourages active participation in decision-making, increases the sense of belonging and appreciation of each school employee, thus having a positive impact on their motivation and work performance. In contrast, authoritarian control, through strict and centralistic control, gradually inhibits creativity and participation and develops resistance and tension. Therefore, it is recommended that the head of the vocational school use democratic and transformational leadership practices in order to improve teaching standards. Vocational school principals use democratic and transformational leadership practices to improve teaching standards.